Effects of Masupirdine (SUVN‐502) on Agitation/Aggression and Psychosis in Patients with Probable Alzheimer's Disease: A Post Hoc Analysis. (20th December 2022) - Nirogi, Ramakrishna; Jayarajan, Pradeep; Abraham, Renny; Tadiparthi, Jayaprakash; Benade, Vijay; Shinde, Anil K; Rasheed, Mohammed Abdul; Badange, Rajesh Kumar; Goyal, Vinod Kumar; Palacharla, Veera Raghava Chowdary; Ravulu, Jyothsna; Jetta, Satish; et al.
Abstract: Background: Alzheimer's disease (AD) is a neurodegenerative disorder in older people with manifestations of cognitive and functional decline and neuropsychiatric symptoms (NPS). Agitation/aggression and psychosis are regarded as the most distressing NPS. Serotonin‐6 receptor (5‐HT6 ) is a G protein‐coupled receptor and is localized almost exclusively in the central nervous system regions which are important for control of mood regulation. Masupirdine is a potent and selective 5‐HT6 receptor antagonist. Masupirdine has been evaluated for its effects on cognition in patients with probable Alzheimer's disease. Method: Masupirdine has been evaluated in a phase‐2a proof‐of‐concept, 26‐week, randomized, double‐blind, placebo‐controlled, multicenter, parallel group clinical study in United States under active US IND. Subgroup analyses of phase‐2a study results was carried out to evaluate the beneficial effects of masupirdine on agitation/aggression, and psychosis using Neuropsychiatric Inventory (NPI‐12) scale. Masupirdine was also evaluated in animal models to assess its effect on behavior and brain neurotransmitter modulations. Result: Masupirdine showed robust efficacy in agitation/aggression scores in patients who had baseline symptoms of agitation/aggression. In patients with baseline psychosis symptoms and/or symptom emergence, a significant reduction in psychosis scores were observed in masupirdine treatment arms. Behavioral observations from the animal models were also in accord with the post hoc observations from the masupirdine clinical trial. Conclusion: Observations from the masupirdine clinical trial suggest the potential utility of masupirdine for the management of neuropsychiatric symptoms associated with agitation/aggression, and psychosis in patients with AD. Masupirdine is currently being evaluated for the management on agitation in patients with dementia of the Alzheimer's type.